Characteristics of hot boned bovine muscle - Kastner, Curtis L.; Henrickson, R.L.; Morrison, R.D. (American Society of Animal Science, 2008)
Six Hereford steer carcasses were assigned tDto each of three holding periods (either 2-, 5- or 8-hr. postmortem). Each carcass was split and one side was "hot" boned into muscles and muscle systems after being held intact for the assigned holding period at 16 C. The corresponding sides were fabricated into the muscles and muscle systems after chilling for 48 hr. at 2 C ("cold" boned). When the sides to be "hot" boned were held intact for 8 hr. postmortem, then fabricated, the "hot" boned steaks were equal or superior to those "cold" boned when the following parameters were compared: shrink (percent loss), shear force, color value notation, flavor, cooking loss, water-binding capacity, percent moisture and fat.
Keywords: Food science; Bovine; Muscle